PENINGKATAN HASIL BELAJAR IPA DENGAN MENGGUNAKAN PENDEKATAN KONSTRUKTIVISME PADA SISWA KELAS IV SD NEGERI 27 RAWANG KECAMATAN SUTERA - Suri ani (Inovasi Pendidikan, 2017)
IPA as one of the subjects in elementary school is a program to inculcate and develop the knowledge, skills, and attitudes scientific value to the students, as well as a sense of love and respect for the greatness of God Most EsaSesuai with the process of learning science that emphasizes providing learning experiences directly to develop their potential in understanding the nature around. Forms of implementation science learning tailored to the steps using a constructivist approach are: the initial activity is to determine the purpose, on core activities tailored to the steps of constructivism, namely: to enable existing knowledge, acquiring new knowledge, understanding of knowledge, applying the knowledge and experience gained , as well as reflections. And at the end of the activities that follow-up and evaluation in accordance with the material already in the learning. By using a constructivist approach to learning science, learning outcomes fourth grade students of SDN 27 Rawang has increased. This increase can be seen the level of mastery in the first cycle reaches 56%, the second cycle increased to 89%. The number of students who achieve mastery in the first cycle of 10 people, and the second cycle increased to 16 students from 18 students. Key words: results learning, science, constructivism approach, students